Hubungan Tingkat Pendidikan Orang Tua terhadap Perilaku Sosial Anak - Rahmah, Rahmah; Armizi, Armizi; Herlinda, Susi; Fatma, Fatma (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2024)
The level of education of parents is an order, level of education, level or order completed by parents during their education. The purpose of the study was to see the relationship between parental education and social behavior. Pre-experimental research design was conducted on 30 parents of children. The data collection technique uses a questionnaire given to the child's parents. The sample set is all parents of children. For data analysis using correlation. From the results of parents' responses to children's social behavior in terms of overall per indicator about parents' responses to children's social behavior classified as